A comprehensive interventional program for promoting father's participation in the perinatal care: protocol for a mixed methods study - Vahideh Firouzan; Mahnaz Noroozi; Ziba Farajzadegan; Mojgan Mirghafourvand (BMC, 2018)
Abstract Background The inclusion of fathers' participation during the perinatal period is an important strategy for improving mothers' health. No studies have yet been conducted in Iran to explain the concept, obstacles and facilitators of fathers' participation during the perinatal period. Thus, this study will be carried out to provide a comprehensive interventional program for promoting fathers' participation in the perinatal care. Methods This study is a sequential exploratory (qualitative - quantitative) mixed methods design that consists of three consecutive phases. In this study, following a qualitative approach, the researchers will explain the concept, obstacles, facilitators and strategies related to promoting fathers' participation in perinatal care. In the second phase, researchers will design an appropriate and comprehensive interventional program for promoting fathers' participation in perinatal care by using the results of the qualitative phase and literature reviews. The proposed interventional program is designed by a panel of experts based on prioritization guidelines and will be finalized for execution. In the third stage, the effectiveness of interventional program on the awareness, attitude and practice of fathers about participation in perinatal care will be investigated in a semi-experimental study. Discussion It is expected that from the results of the present mixed methods study, by presenting an interventional culturally sensitive program which is appropriate for the conditions of the society for expectant fathers, the participation of fathers in the perinatal period will increase and thus lead to improvements in the health of the mother and the infant. If this interventional program is effective, it could be included in the perinatal health care guidelines. Trial registration IRCT20160224026756N4 Registered 27 May 2018.